Tiktok App Use on Children's Mental Health: An Overview of Educational Psychology - Khairunnisa Ulfadhilah; Salsabila Dwi Nurkhafifah (Academicus: Journal of Teaching and Learning, 2025)
This study aims to explore the impact of the use of the TikTok application on the mental health of children in RA Mubarokah through a qualitative descriptive approach. The TikTok application, as a popular social media platform, offers a variety of content that can affect children's psychological development. This research method involves in-depth interviews with parents, teachers, and children as well as observations to collect data about their interactions with the app. The results of the study show that the use of TikTok has both positive and negative impacts. On the one hand, children stated that this app provides entertainment and boosts creativity through various challenges and interesting content. However, on the other hand, there are concerns about social pressure, social comparisons, and the negative impact on children's self-esteem due to exposure to unrealistic content. In conclusion, the TikTok app can be a beneficial tool for children if used wisely. The existence of the Tiktok application in Indonesia has a positive and negative impact, namely getting domestic and foreign information quickly, but it has a negative impact, namely children can reach and even watch continuously, which results in children's growth and development not being optimal, and children do not have to socialize with the environment. Collaboration between parents, educators, and children is needed to create a healthy digital environment, so that the positive impact can be maximized and the negative impact is minimized. This research provides important insights for the development of education and psychology policies to support children's mental health in the digital era.